Poprawność i precyzja treści matematycznych w podręcznikach ekonomii - Klepacz, Halina; Porazińska, Elżbieta; Żółtowska, Elżbieta (Correctness and Precision of Mathematical Content in Economic Manuals, 2006)
The aim of the article is indication and handling of mathematical inaccuracy in illustrations, notations and interpretations of economic relations an actual examples chosen from academic manuals for teaching micro and macro economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 84-89